Penciptaan Busana Feminine Romantic Style Terinspirasi dari Bunga Celosia Cristata - Annisa Rizki; Desi Trisnawati; Novina Yeni Fatrina; Fadri Rahmat (INDO PUBLISHING, 2026)
designers in creating clothing that has a strong aesthetic value and character. One of the fashion styles that remains in demand today is the Feminine romantic style. This style displays a soft, graceful impression, through silhouettes, decorative, and soft color choices. The work entitled